Modeling Groundwater Flow and Contaminant Transport - Bear, Jacob; Cheng, Alexander H.-D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
In many parts of the world, groundwater resources are under increasing threat from growing demands, wasteful use, and contamination. To face the challenge, good planning and management practices are needed. A key to the management of groundwater is the ability to model the movement of fluids and contaminants in the subsurface. The purpose of this book is to construct conceptual and mathematical models that can provide the information required for making decisions associated with the management of groundwater resources, and the remediation of contaminated aquifers. The basic approach of this book is to accurately describe the underlying physics of groundwater flow and solute transport in heterogeneous porous media, starting at the microscopic level, and to rigorously derive their mathematical representation at the macroscopic levels. The well-posed, macroscopic mathematical models are formulated for saturated, single phase flow, as well as for unsaturated and multiphase flow, and for the transport of single and multiple chemical species. Numerical models are presented and computer codes are reviewed, as tools for solving the models. The problem of seawater intrusion into coastal aquifers is examined and modeled. The issues of uncertainty in model input data and output are addressed. The book concludes with a chapter on the management of groundwater resources. Although one of the main objectives of this book is to construct mathematical models, the amount of mathematics required is kept minimal. - Most comprehensive book on mathematical modeling of groundwater flow and contaminant transport - Deep insight into the physics at the microscopic level and its description as averaged processes - Addresses uncertainty and management issues - Written by one of the most highly cited authors of groundwater books (Dynamics of Fluids in Porous Media, and Hydraulics of Groundwater) Audience: Graduate and upper level undergraduate students who are interested in such topics as groundwater, water resources and environmental engineering; of interest to researchers, to scientists, and to professionals who face the need to build and solve models of flow and contaminant transport in the subsurface.
Groundwater and Aquifers -- Regional Groundwater Balance -- Groundwater Motion -- Water Balance and Complete Flow Model -- Unsaturated Flow Models -- Modeling Contaminant Transport -- Numerical Models and Computer Codes -- Seawater Intrusion -- Modeling Under Uncertainty -- Optimization, Inverse, And Management Tools.
Keywords: Geography; Geochemistry; Hydraulic engineering; Mathematical geography; Engineering; Civil engineering; Earth Sciences; Hydrogeology; Computational Intelligence; Mathematical Modeling and Industrial Mathematics; Civil Engineering; Mathematical Applications in Earth Sciences; Geochemistry